Prevalence of hepatitis-B surface antigen among population of inmates in Tihar Jail, New Delhi - Rana, Shweta; Girdhar, Narinder K.; Gill, Manmeet K.; Kumar, Arun (International Journal of Research in Medical Sciences, 2017)
Background: Hepatitis B Virus (HBV), a DNA virus with a human only reservoir, is a worldwide public health problem. Unlike other countries especially Europe and America, there is scarcity of published data on HBV infection among prison inmates in India despite its tremendous importance in public heath formulation compared to the general population. The present study was designed to investigate the prevalence of Hepatitis B surface antigen among population of Jail inmates (convicts). Methods:The study population comprised of all the 1102 prison inmates who were screened for Hepatitis B surface antigen (HBsAg) status using one step immunochromatographic array [INSTACHK Hepatitis-B]. Seroprevalence rate of seropositive was calculated and stratified by age and sex. The seropositives were further subjected to HBeAg and anti-HBe detection, HIV status, anti HCV status, HBV-DNA levels and Liver function tests (LFTs) and the patients were then classified into three groups based on HBV-DNA levels and alanine amino transferase (ALT) levels. Results:Out of 1102 inmates screened, 30 (2.72%) were HBsAg positive. Slightly higher percentage prevalence of HBsAg was found among males i.e., 3.19% (or 27/844) than females i.e., 1.16% (or 3/258). Out of 30 HBsAg positive cases, 16 were HBeAg negative, 8 were HBeAg positive and 6 refused to get investigated further. Ten of the 16 HBeAg negative cases were further subjected to anti HBe detection. Half of these cases (5) were reactive for anti-HBe. Based on HBV DNA levels and ALT levels, 8 patients were categorized as HBeAg positive chronic hepatitis-B patients, 12 patients were categorized as HBeAg negative chronic Hepatitis-B patients and 4 patients as inactive HBsAg carriers. Conclusion:HBsAg prevalence among Tihar Jail inmates is comparable to that among the non-incarcerated general population in India.